Record of the ancient martian hydrosphere and atmosphere preserved in zircon from a martian meteorite - Nemchin, Alexander; Humayun, M.; Whitehouse, M.; Hewins, R.; Lorand, J.; Kennedy, Allen; Grange, Marion; Zanda, B.; Fieni, C.; Deldicque, D. (Nature Publishing Group, Macmillan Publishers Ltd, 2014)
Mars exhibits ample evidence for an ancient surface hydrosphere. The oxygen isotope compositions of carbonate minerals and alteration products in martian meteorites suggest that this ancient hydrosphere was not in isotopic equilibrium with the martian lithosphere1–4. Martian meteorite NWA 7533 is composed of regolith breccia from the heavily cratered terrains of ancient Mars and contains zircon grains for which U–Pb ages have been reported5. Here we report variations between the oxygen isotopic compositions of four zircon grains from NWA 7533. We propose that these variations can be explained if the mantle melts from which the zircon crystallized approximately 4.43Gyr ago had assimiliated 17 O-enriched regolith materials, and that some of the zircon grains, while in a metamict state, were later altered by low-temperature fluids near the surface less than 1.7Gyr ago. Enrichment of the martian regolith in 17O before the zircon crystallized, presumably through exchange with the 17O-enriched atmosphere or hydrosphere during surface alteration, suggests that the thick primary atmosphere of Mars was lost within the first 120Myr after accretion. We conclude that the observed variation of 17O anomalies in zircon from NWA 7533 points to prolonged interaction between the martian regolith, atmosphere and hydrosphere.